Using phyto- and carotene containing raw material sinemulsion –type sauces technology - Liavynets, Heorhii; Havrysh, Andrey; Niemirich, Oleksandra; Arsenieva, Larisa; Kokhan, Olena M. (My University, 2013)
The abstract states the necessity of using phyto- and carotene containing raw materials in emulsion –type sauces for improving their quality and biological value.
Keywords: соуси; β-каротин; полісахариди; майонез; соусы; β-каротин; полисахариды; майонез; sauces; β-carotene; polysaccharides; mayonnaise; кафедра експертизи харчових продуктів; кафедра іноземних мов професійного спрямування; кафедра технології ресторанної і аюрведичної продукції; кафедра готельно-ресторанної справи